The Reality of the Second Field’s Teachers Practice of the Augmented Reality Technology in Teaching Sciences in order to develop higher thinking skills in Ash Sharqiyah South Governorate in Oman - Al-Mashaikhi, Basma Nasser Mohammed; Mai, Mohammed Mai (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the extent to which the teachers of the second field practice augmented reality technology in science teaching to develop higher-order thinking skills (analysis, evaluation and creativity) among students of the first cycle, in the Governorate of South Al Sharqiyah in the Sultanate of Oman was average (M=2.92, SD= 0.75) in their opinion. The study also stated that differences are statistically significant (α=0.05) in the reality of teachers practice of this technology in developing higher thinking skills according to teachers’ teaching experience (F= 3.78 df, 192،3) in favor of Female teachers with less experience for the category of female teachers less than 5 years and the category of female teachers from 5 years to less than 10 years With regard to the training variable, the value of (T = 2.92) and the degree of freedom = (194) was in favor of the female teachers who joined the training program. The Study recommended to provide the infrastructure that supports the employment of technology in the educational process in addition to develop the Curricula in order to direct male and female teachers towards the use of augmented reality technology in teaching and to continuously qualify and train male and female teachers with training courses that contribute to the development of their technical skills in light of the rapid developments of augmented reality technology applications and their employment in teaching.